LEXICOGRAPHIC PRINCIPLES OF STUDYING DOMAIN-SPECIFIC TERMINOLOGY IN ENGLISH AND UZBEK - Ergashev, Muhammadjon (QO‘QON UNIVERSITETI XABARNOMASI, 2026)
This article examines the lexicographic principles for arranging field-specific terminological translation dictionaries, focusing on English-Uzbek bilingual resources. It addresses the relevance of terminology standardization in translation and knowledge dissemination, identifying gaps in current Uzbek lexicography. The study reviews major theoretical frameworks from international and local scholars, applying comparative, lexicographic, and terminological analyses to selected dictionaries. Results highlight the dominance of alphabetical arrangements, hybrid models, microstructure components such as equivalents and definitions, and challenges including equivalence gaps and inconsistencies. The discussion interprets these findings against international standards, offering implications for terminology management and dictionary compilation. Conclusions summarize key insights and provide recommendations for enhancing Uzbek-English terminological dictionaries.